Nature of Science and Philosophy of Science in Education: a Dialogue based on Philosophy Textbooks (Revista Brasileira de Pesquisa em Educação em Ciências, 2022)
The comprehension of the nature of science (NOS) is widely accepted as a fundamental component of scientific literacy and a central goal in science education. At the same time, the teaching of Philosophy (including philosophy of science) is present in pre-college education in different countries, Brazil being among them. However, little has been discussed concerning the possible interplay between these two fields and its implications. The present study investigates the topics on philosophy of science addressed by Philosophy textbooks included in the National Textbook Program 2018 by means of content analysis. The convergences and divergences between the images of science conveyed by the textbooks and the literature on NOS are discussed. The need for further dialogue between science and Philosophy education, both in school practice and research, is pointed out.